Implementation Johari Window Technique With Intervention Individual Counseling (Client Centered Counseling) For Growth Of Self-Acceptance In Vocational High School X In Gresik - Jihan Sabila Ishmah; Nadhirotul Laily; Awang Setiawan Wicaksono (Universitas Muhammadiyah Banjarmasin, 2022)
The problem with this study is the self-acceptance in Vocational High School. The purpose of this study is to know the use of assessment johari window techniques and individual counseling interventions with the centered person approach to cope low self-acceptance. This type of research is an experiment for one group design pre-test and post-test, data analysis techniques using comparison tests. The subject of this study are the class x students